SISTEM PERLADANGAN BERPINDAH SEBAGAI LOCAL GENIUS PADA MASYARAKAT BUKIT DI PEGUNUNGAN MERATUS, KALIMANTAN SELATAN - Hidayat, Yusuf (Vidya Karya Jurnal Kependidikan, 2013)
This article has the objective to state that farming by moving is not the cause of ecological disaster. Such activity is the local genius that is done and developed by masyarakat Bukit di Mount Meratus in order to keep the nature and human being. However, the change of society orientation in planting commercial plant has created the problems and dillema in masyarakat Bukit di Mount Meratus.